Association of Granulomatosis With Polyangiitis (Wegener's) With HLA–DPB1*04 and SEMA6A Gene Variants: Evidence Grom Genome‐Wide Analysis. Issue 9 (26th August 2013) - Xie, Gang; Roshandel, Delnaz; Sherva, Richard; Monach, Paul A.; Lu, Emily Yue; Kung, Tabitha; Carrington, Keisha; Zhang, Steven S.; Pulit, Sara L.; Ripke, Stephan; Carette, Simon; Dellaripa, Paul F.; et al.
<x xml:space="preserve">Abstract</x> Objective To identify genetic determinants of granulomatosis with polyangiitis (Wegener's) (GPA). Methods We carried out a genome‐wide association study (GWAS) of 492 GPA cases and 1, 506 healthy controls (white subjects of European descent), followed by replication analysis of the most strongly associated signals in an independent cohort of 528 GPA cases and 1, 228 controls. Results Genome‐wide significant associations were identified in 32 single‐nucleotide polymorphic (SNP) markers across the HLA region, the majority of which were located in the HLA–DPB1 and HLA–DPA1 genes encoding the class II major histocompatibility complex (MHC) DPβ chain 1 and DPα chain 1 proteins, respectively. Peak association signals in these 2 genes, emanating from SNPs rs9277554 (for DPβ chain 1) and rs9277341 (DPα chain 1) were strongly replicated in an independent cohort (in the combined analysis of the initial cohort and the replication cohort, P = 1.92 × 10−50 and 2.18 × 10−39, respectively). Imputation of classic HLA alleles and conditional analyses revealed that the SNP association signal was fully accounted for by the classic HLA–DPB1*04 allele. An independent single SNP, rs26595, near SEMA6A (the gene for semaphorin 6A) on chromosome 5, was also associated with GPA, reaching genome‐wide significance in a combined analysis of the GWAS and replication cohorts (P = 2.09 × 10−8). Conclusion We identified the SEMA6A and HLA–DP loci as significant contributors to risk for GPA, with the HLA–DPB1*04 allele almost completely accounting for the MHC association. These two associations confirm the critical role of immunogenetic factors in the development of GPA.